2020
DOI: 10.1111/jdv.16642
|View full text |Cite
|
Sign up to set email alerts
|

Validity of EQ‐5D‐5L, Skindex‐16, DLQI and DLQI‐R in patients with hidradenitis suppurativa

Abstract: Background Numerous generic, skin-and disease-specific health-related quality of life (HRQoL) measures are available for patients with hidradenitis suppurativa (HS). Yet, robust psychometric evidence is lacking in many aspects of these outcome measures. Objectives We sought to determine convergent and known-groups validity of multiple generic and skin-specific HRQoL measures and to identify predictors of impaired HRQoL in patients with HS. Methods Between 2017 and 2019, a multicentre cross-sectional study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 59 publications
(132 reference statements)
4
31
0
Order By: Relevance
“…Furthermore, we did not have any information on the treatment history of these patients. Several earlier studies from Hungary confirmed that successful treatment and management of skin diseases improve health-related quality of life and well-being of patients [9,[54][55][56][57][58][59]. Fourthly, in absence of a Hungarian value set for the ICECAP-A, our analyses relied on the ICECAP-A value set for the UK and not that of the Hungarian population, whose values may differ across attributes and levels.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, we did not have any information on the treatment history of these patients. Several earlier studies from Hungary confirmed that successful treatment and management of skin diseases improve health-related quality of life and well-being of patients [9,[54][55][56][57][58][59]. Fourthly, in absence of a Hungarian value set for the ICECAP-A, our analyses relied on the ICECAP-A value set for the UK and not that of the Hungarian population, whose values may differ across attributes and levels.…”
Section: Discussionsupporting
confidence: 52%
“…Additionally, it is used as a primary endpoint in ongoing clinical studies with an interleukin-23 blocker, tildrakizumab for the treatment of psoriasis [ 54 , 55 ]. Although the DLQI-R is equally good or even better in many aspects of measurement properties than the DLQI [ 12 , 52 , 53 ], it cannot settle all issues around the underlying construct of the original questionnaire (e.g. DIF).…”
Section: Discussionmentioning
confidence: 99%
“…Between September 2017 and October 2019, we carried out a cross-sectional survey at three academic dermatology clinics in Hungary [40]. The inclusion criteria to this study were as follows: (i) ≥ 18 years of age; (ii) cognitive ability to understand the questionnaire; (iii) diagnosis of HS by a dermatologist; and (iv) signing a consent form prior to the data collection.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%